Strengthening and flame retarding effect of bamboo fiber modified by silica aerogel on polylactic acid composites. (18th July 2022) - Niu, Qianqian; Yue, Xiaopeng; Guo, Zhenghong; Fang, Zhengping; Li, Juan
Graphical abstract: Strengthening and flame retarding effects on PLA/BF composites are achieved using BF modified by silicon aerogel. Highlights: BF was treated using silica aerogel to obtain IBF-Si. The IBF-Si decreases the thermal conductivity of PLA/IBF-Si composites, and suppresses the "wick effect" of BF in PLA. PLA/IBF-Si composites have better flame retardancy than that of PLA/BF composites. PLA/IBF-Si composites have better tensile and impact strength than that of PLA/BF composites. Abstract: Weak interfacial adhesion and inflammability of bamboo fiber (BF) reinforced poly (lactic acid) (PLA) composites restricts its application in construction field. In this paper, BF was modified by using 3-isocyanatopropyltrimethoxysilane (IPMS) firstly, and then reacted with tetraethyl orthosilicate (TEOS) to obtain BF modified by silica aerogel which is marked as IBF-Si. The IBF-Si and ammonium polyphosphate (APP) were used to improve the mechanical and flame retardant properties of PLA. The results showed that 20 wt% IBF-Si and 10 wt% APP make PLA achieve the UL-94-V0 and a LOI of 36.4 vol%, while PLA with 20 wt% BF and 10 wt% APP just obtain the UL-94-V2, and a LOI of 27.8 vol%. Moreover, the tensile and impact strength are improved greatly, after introducing 1 wt% IPMS into PLA/IBF-Si the mechanical properties are improved more indicating better interface adhesion between PLA and IBF-Si. In addition, the IBF-Si decreases the thermal conductivity of PLA/IBF-Si composites, and suppresses the "wick effect" of BF. Meanwhile, the IBF-Si promotes the char formation of APP which is helpful to prevent the exchange of heat and oxygen between the environment and resin. Thus both mechanical and flame retardant properties are improved.